Analisis Hukum Ekonomi Syari’ah dan Hukum Positif terhadap Kerusakan dalam Sewa-Menyewa Kost : Studi di Wisma Karnetta Putri Sukarame Bandar Lampung - Dina Agustin; Yufi Wiyos Rini Masykuroh; Olivia Rizka Vinanda (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
The practice of mu'amalah activities has renting (ijarah). So in this study about the rent of the Wisma Karnetta Putri boarding house located at Gg. Nuja 1, Way Dadi Village, Sukarame District, Bandar Lampung. The main problem in this study is that there is an agreement that is not in accordance with the agreement at the beginning of the ijarah contract or rent, namely the action of the boarding house owner who coerces The tenant reimburses the damage to the facilities or items of the boarding house even though the damage is not to the tenant's fault. The formulation of the problem in this study is what are the damages incurred by tenants at Wisma Karnetta Putri Sukarame Bandar Lampung and how is . The purpose of this study is to find out What are the damages incurred by tenants at Wisma Karnetta Putri Sukarame Bandar Lampung and to find out how the Analysis of Sharia Economic Law and Positive Law on Damage in Renting a Boarding House (Study at Wisma Karnetta Putri Sukarame Bandar Lampung). The method used by the researcher in the study is a qualitative method that includes which is borne by tenants at Wisma Karnetta Putri Sukarame Bandar Lampung and to find out how the Analysis of Sharia Economic Law and Positive Law on Damage in Renting a Boarding House (Study at Wisma Karnetta Putri Sukarame Bandar Lampung). The methods used by the researcher in the research are qualitative methods that are included in field research and data collection techniques through interviews and documentation. The results of the research on the practice of renting a boarding house on the damage to renting a boarding room borne by the tenant at Wisma Karnetta Putri Sukarame Bandar Lampung are in the form of damage to the well water pump machine, lights that go off caused by lightning, and damaged water faucets, and in the lease contract (ijarah) there are boarding house rental activities that are detrimental to other parties, namely the tenant, Because the tenant of the boarding house must replace the damage to the boarding facility even if the damage This is not due to the tenant's fault.